Теплый дождь: повести / Виктор Александровский - Александровский Виктор Николаевич (Современник, 1986)
Экземпляры: РБ (20181031ԁ) / Инвентарный номер: 25933 / Цена: 01.60 / Авт.знак: А46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6